Odpowiedź :
1) -(x+3)-(2x+8)=1
-x-3-2x-8=1
-3x-11=1
-3x=12/-3
x=-4
-
3)-3+13+2x=4x-15
2x-4x=3-13-15
-2x=-25
x=12.5
-x-3-2x-8=1
-3x-11=1
-3x=12/-3
x=-4
-
3)-3+13+2x=4x-15
2x-4x=3-13-15
-2x=-25
x=12.5
1)-(x+3)-(2x+8)=1
-x-3-2x-8=1
-3x-11=1
-3x=12 / :(-3)
x=-4
3) -3+13+2x=4x-15
10+2x=4x-15
25=2x / :2
x=12,5
6)2x-3x-7=x+1
-x-7=x+1
-2x=8 / :(-2)
x=-4
7)3x+4- x/5=x-1 / *5
15x+20-x=5x-5
9x=25 / :9
x=25/9
/-kreska ułamkowa
-x-3-2x-8=1
-3x-11=1
-3x=12 / :(-3)
x=-4
3) -3+13+2x=4x-15
10+2x=4x-15
25=2x / :2
x=12,5
6)2x-3x-7=x+1
-x-7=x+1
-2x=8 / :(-2)
x=-4
7)3x+4- x/5=x-1 / *5
15x+20-x=5x-5
9x=25 / :9
x=25/9
/-kreska ułamkowa
1) -(x+3)-(2x+8)=1
-x-3-2x-8=1
-3x=12 /: (-3)
x= 4
2)-2(x+5)+7(x-3)=-6
-2x-10+7x-21=-6
5x=25 /:5
x=5
3)-3+13+2x=4x-15
2x-4x= -15+3-13
-2x= -25 /: (-2)
x= 12 1/2
-x-3-2x-8=1
-3x=12 /: (-3)
x= 4
2)-2(x+5)+7(x-3)=-6
-2x-10+7x-21=-6
5x=25 /:5
x=5
3)-3+13+2x=4x-15
2x-4x= -15+3-13
-2x= -25 /: (-2)
x= 12 1/2